Respiratory syncytial virus subtypes in children with bronchiolitis: does it correlate with clinical severity? - Shuo Yang; Sukun Lu; Yakun Wang; Yinghui Guo; Zhuang Zhang; Weijian Wang; Le Wang (BMC Infectious Diseases, 2024)
Abstract Background In this retrospective study, we aimed to evaluate the factors associated with the severity of respiratory syncytial virus (RSV) bronchiolitis in children aged under 2 years who were admitted to the Children’s Hospital of Hebei between June 2018 and January 2019. Methods Sputum samples positive for RSV via multiplex PCR were subtyped using real-time PCR. Data collected included risk factors for disease severity, demographics, microbiology, and outcomes. Results Of the 82 children with RSV bronchiolitis, 79 were treated and discharged with improvement, while 3 died. All three patients had underlying medical conditions, including complex congenital heart disease and severe combined immunodeficiency. Further, disease severity was associated with preexisting underlying disease, fever duration, and bacterial co-infection, but not with the RSV subtype. Conclusions Our findings suggest that an appropriate therapeutic regimen should include the detection of bacterial co-infections and the identification of underlying diseases for the effective management of severe RSV bronchiolitis.